CUSTOMER SATISFACTION DITINJAU DARI PENGGUNAAN M-BANKING DAN RELIGIOUS ACTIVITY BANK SYARIAH INDONESIA KOTA BENGKULU - Aan Shar; Faisal Muttaqin; Eko Wediyanto (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2023)
The purpose of this study was to determine customer satisfaction of Bank Syariah Indonesia (BSI) Bengkulu City in terms of the use of M-Banking and religious activity. Researchers used an associative quantitative approach with the sampling technique used, namely Non-Probability Sampling with the Purposive Sampling method. The primary data collection technique is in the form of a questionnaire which has been distributed to 69 respondents. The data analysis technique used multiple linear regression analysis using the SPSS version 25 program. The results showed that the variable using M-Banking had a positive and significant effect on customer satisfaction with a coefficient value of 0.002 and a significance value of 0.05. Then, the results of the study show that the variable religious activity has a positive and significant effect on customer satisfaction with a coefficient value of 0.000 and a significance value of 0.05. And the results of the study also show that the variable use of M-Banking and religious activity has a positive and significant effect on customer satisfaction with a coefficient value of 0.000 and a significance value of 0.05. The results of the test for the coefficient of determination also explain that both have a fairly strong effect of 89%.